1977
DOI: 10.2151/jmsj1965.55.5_518
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Products of a Splashing Water Drop

Abstract: The physical products of splashing water drops were investigated with respect to several parameters: impact velocity, drop size, surface tension, radius of curvature and roughness of the target surface, and the depth of liquid film covering the surface of the target. It is shown that the number of droplets produced by a splash increases with surface roughness, impact velocity and drop size, but decreases with an increase in liquid film depth and with a reduction in surface tension of the drop. For a given drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 11 publications
3
55
0
Order By: Relevance
“…The correlations are in good agreement in comparison to experimental data [15] [24]. Ejection angles of the secondary droplets are typically in the range of α 10 AE to α 15 AE relative to the wall whereas initial velocities are about 60% of the impact value.…”
Section: Wall Interactionsupporting
confidence: 75%
“…The correlations are in good agreement in comparison to experimental data [15] [24]. Ejection angles of the secondary droplets are typically in the range of α 10 AE to α 15 AE relative to the wall whereas initial velocities are about 60% of the impact value.…”
Section: Wall Interactionsupporting
confidence: 75%
“…The impact of a liquid drop onto a rigid surface results in a rapid sequence of events ending, in the inertial limit, in spreading (Eggers et al 2010) or splashing (Stow & Hadfield 1981), interface tearing (Villermaux & Bossa 2011) and ultimate fragmentation (Stow & Stainer 1977). A large number of studies have investigated the many facets of drop impact, with a special attention to the description of its late stages (Rein 1993;Yarin & Weiss 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship is superior to that proposed by Stow and Stainer (1977) in that it provides the correct functional relationship between R and VT, and correctly predicts values of N observed by Stow and Stainer. For drops impacting at their terminal velocity, the effect of the roughness of the target is believed to be crucial in predicting the occurrence of a splash only if drops possess radii in the range 0.5-0.8mm; for smaller drops no splash is likely, even on a very rough surface, and larger drops will splash on a perfectly smooth surface.…”
Section: Introductionmentioning
confidence: 46%
“…In particular, she noted that the impacts she observed with a polished metal surface produced no splash products; Levin and Hobbs (1971) in their study of the hydrodynamics and charge separation effects associated with drop impacts, avoided the use of smooth targets for this reason. Stow and Stainer (1977), on the other hand, used a direct method of droplet collection to determine the numbers and sizes of the splash products and they were able to establish certain empirical relationships between these data and the initial conditions of the splash as determined by the impact velocity, drop size, surface tension, and the radius of curvature and the roughness of their metal targets. For a flat target, described as being "medium rough", they found that the number of droplets N ejected during a splash could be estimated by an expression of the form N=3.4 R3V2-63 provided the radius of the impacting drop R(mm) and the velocity of impact V(ms-1) are known.…”
Section: Introductionmentioning
confidence: 99%